Immobilization of Leuconostoc-paramesenteroides Dextransucrase Enzyme and Characterization of its Enzyme Properties - Amal M. Hashem,; Mona A. El-Refaei,; Hasan M. Gebril ,; Ahmed F. Abdel-Fattah, (Journal of Basic & Applied Sciences, 2012)
Dextransucrase from Leuconostoc-paramesenteroides was immobilized using different immobilization techniques. Entrapment in calcium alginate (2%) proved to be the most suitable technique (27.6% yields). The operational stability of the immobilized was retained 100% until 11 cycle, with decreasing of 70%, of the retained activity at 13 cycles. The specific activity of the free was compared to that of the immobilized enzyme. The optimum temperature of the free enzyme was 65°C were as it was 70°C with the immobilized enzyme. The specific activity of the immobilized was higher than that of the free enzyme at pH 4. 100% of the specific activity was retained due to the thermal stability of the immobilized enzyme after heat treatment for 60 minutes at 60°C. The activation energy (EA) of the immobilized enzyme was lower than that of the free enzyme (EA= 10.3 and 12.13 Kcal/mol respectively). The calculated half-lives of the free enzyme at 40, 50, 60 and 70 were 15.0, 4.68, 4.68 and 4.0 min respectively which were lower than those of immobilized enzyme i.e. 401, 385, 295 and 42 min, respectively.